2019
DOI: 10.1007/s40134-019-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Detection and Diagnosis: Role of Ultrasound with MRI Correlates

Abstract: Purpose of Review Prostate cancer (PCA) detection and diagnosis has rapidly changed in recent years, with medical imaging playing an instrumental component. Multiparametric magnetic resonance imaging (MRI) has led to an alternative diagnostic pathway for patient triage and diagnosis. Ultrasound (US) is already essential to this pathway, and development of new US technologies ensures it will assume an even more important role. Recent Findings Conventional US is widely used for anatomic guidance during prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“… 71 73 When visible on ultrasound, cancers most often appear hypoechoic 74 because they reflect significantly less sound echoes than normal tissue. To supplement grayscale ultrasound, other new ultrasound-based imaging techniques such as shear-wave elastography, 75 77 color doppler ultrasound, 77 contrast-enhanced ultrasound, 78 micro-ultrasound, 79 and their combination have been proposed. These alternative ultrasound-based imaging modalities provide enhanced image resolution and better visualization of the prostate compared to grayscale ultrasound, and enable prostate cancer detection with better sensitivity compared to grayscale ultrasound.…”
Section: Ai Models For Prostate Cancer Detection and Characterizing C...mentioning
confidence: 99%
“… 71 73 When visible on ultrasound, cancers most often appear hypoechoic 74 because they reflect significantly less sound echoes than normal tissue. To supplement grayscale ultrasound, other new ultrasound-based imaging techniques such as shear-wave elastography, 75 77 color doppler ultrasound, 77 contrast-enhanced ultrasound, 78 micro-ultrasound, 79 and their combination have been proposed. These alternative ultrasound-based imaging modalities provide enhanced image resolution and better visualization of the prostate compared to grayscale ultrasound, and enable prostate cancer detection with better sensitivity compared to grayscale ultrasound.…”
Section: Ai Models For Prostate Cancer Detection and Characterizing C...mentioning
confidence: 99%
“…Zhang Cancer detection rate of TRE may also depend on Gleason scores as higher scores represent increased cell density and stiffness, thus the higher sensitivity of TRE. 16 Addition of TRE targeted biopsy to standard biopsy can increase prostate cancer detection rate. Schiffman et al also found high specificity (90.9%) of elastography targeted prostate biopsy.…”
Section: Resultsmentioning
confidence: 99%
“…Simple and Neural stimulation on normal and cancerous prostate tissue and the reaction of the tissues used to investigate the presence or absence of the mass. Since the prostate tissue is symmetrical and the characteristics of forming cancerous masses are similar to the prostate tissue, 26 to analyze the neural stimulation velocity and frequency on the tissue, neural stimulation applied to the prostate gland at 0, 5, and 10 Hz with different velocities. Once again, it was placed on the spherical zone of the prostate gland; and the conditions of the previous states repeated.…”
Section: Methodsmentioning
confidence: 99%